Alkylpolyglycoside modified MnFe2O4 with abundant oxygen vacancies boosting singlet oxygen dominated peroxymonosulfate activation for organic pollutants degradation. (December 2021) - Zhou, Rui; Liu, Shuai; He, Fangru; Ren, Hejun; Han, Zhonghui
Abstract: A novel alkylpolyglycoside (APG)-modified MnFe2 O4 nanocomposite (APG@MnFe2 O4 ) enriched with oxygen vacancies (VOs) was developed via co-precipitation and characterized as a peroxymonosulfate (PMS) activator to degrade 2, 4-dichlorophenol (2, 4-DCP) as the model contaminant. The APG effectively promoted the in situ formation of VOs on MnFe2 O4 and subsequently enhanced the production of singlet oxygen ( 1 O2 ). Furthermore, the APG@MnFe2 O4 initialized an even more efficient non-radical pathway and dominated the degradation of 2, 4-DCP. The constructed APG@MnFe2 O4 exhibited a much higher reaction rate constant (0.0522) by 12.73 times of that of the bare MnFe2 O4 (0.0041). The degradation efficiency of 2, 4-DCP in the APG@MnFe2 O4 /PMS system approached 93% within 90 min, a rate significantly higher than that in the MnFe2 O4 /PMS system (32%) given the same condition. The reasonable catalytic mechanism can be attributed to the Fe/Mn/VOs species. The APG@MnFe2 O4 also exhibits universally high removal activity for various pollutants and excellent cyclic stability. Thus, the APG@MnFe2 O4 is a promising PMS activator, and its utilization offers a useful strategy for developing VOs-enriched MnFe2 O4 catalysts as a means of eliminating organic pollutants from wastewater. Highlights: A novel APG modified MnFe2 O4 was developed as a PMS activator. The APG in the synthesis process enriched VOs in MnFe2 O4。 . The enhanced 1 O2 dominated the degradation of 2, 4-DCP. A strategy for developing VOs-enriched MnFe2 O4 catalysts was provided.